Comparing UK and Other Western Countries' Health Expenditure, Relative Poverty and Child Mortality: Are British Children Doubly Disadvantaged?. (5th May 2014) - Pritchard, Colin; Wallace, Mark S
<x xml:space="preserve">Abstract</x> We examined the UK's effectiveness in reducing Child Mortality with 20 other Western countries, in the context of their national health expenditures, and, relative poverty — measured by 'Income Inequality' the gap between top and bottom 20 per cent of income. W.H.O. Child (0–14) Mortality Rates (CMR) and GDP Expenditure on Health (% GDPHE) were examined and a cost‐effectiveness ratio calculated, which is the reduced CMR over the period divided by average GDPHE. The highest average % GDPHE was USA at 13.2 per cent; the UK's 7.3 per cent was equal lowest. The widest Income Inequality was USA 8.5 times; the UK at 7.2 was third widest. The highest CMR was the USA 2436 per million (pm), the UK's 1630 pm, although representing a fall of 62 per cent was fourth highest. However, UK cost‐effectiveness ratio (1: 350) was eighth best of 21 countries. Only Income Inequality correlated significantly with CMR. UK CMR fell significantly more than five countries but ten others declined more. If UK deaths had been at the average of the 17 countries with lower CMR, there would have been 1827 fewer deaths. British children's poverty and health expenditure means they and their services are doubly disadvantaged although the NHS relatively achieved more with comparatively less.